Revision of genus Repipta Stål 1859 (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) with new species and distribution data - Martin-Park, Abdiel; Delfín-González, Hugo; Del Carmen Coscarón, María (Zootaxa, 2012)
A revision was made of Repipta Stål, mostly a Neotropical genus with some species in the Neotropics and the Nearctic. Thirteen known species are redescribed: R. annulipes Barber, R. antica Stål, R. coccinea (Herrich-Schaeffer), R. flavicans (Amyot & Serville), R. fuscospinosa Stål, R. fuscipes Stål, R. lepidula Stål, R. mucosa Champion, R. nigronotata Stål, R. obscuripes Stål, R. sexdens (Fabricius), R. spinosa (Fabricius), and R. taurus (Fabricius). Twelve new species are described and illustrated, including data on male and female genitalia, new distributional records, and key to the species.